Influence of milk. levels of beef cows on returns:a simulation approach - Schalles, R.R.; Zoellner, K.O.; Clarke, L.S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Results of four simulated production systems indicated that high levels of milk produced calves that were heavier at weaning, primarily because of an increase in body fat. High levels of milk production, however, were a disadvantage when calves went directly to the feedlot. With slow-growing calves, the fat either had to be depleted postweaning, or the calves had to be slaughtered at less-than-desirable weights in order to maintain desirable carcass fat. High milk intake is more tolerable for calves with fast growth rates, whereas low milk intake is a an economic necessity for calves with slow growth rates. The moderate size (1250 lbs), moderate milking (average of 16.6 lbs per day) cows produced the greatest return over feed cost.
Keywords: Beef; Milk levels; Simulation; Beef cows